Highly Comminuted, Articular Fractures of the Distal Antebrachium Managed by Pancarpal Arthrodesis in 8 Dogs. Issue 1 (28th October 2015) - Brown, Gordon; Kalff, Stephen; Gemmill, Toby J.; Pink, Jonathan; Oxley, Bill; McKee, W. Malcolm; Clarke, Stephen P.
Abstract : Objective: To describe the surgical management by pancarpal arthrodesis for highly comminuted articular fractures of the distal antebrachium in 8 dogs. Study Design: Retrospective clinical case series. Animals: Eight dogs. Methods: Medical records (2001–2014) of dogs with antebrachial fractures were reviewed and dogs with highly comminuted distal antebrachial fractures were identified. The nature of the injury, surgical management by pancarpal arthrodesis, outcome, and complications were recorded. Results: Nine fractures occurred in 8 dogs. Seven dogs were ex‐racing greyhounds (8 fractures) and of these, 6/7 dogs had fractures of the right thoracic limb. Compared with the hospital population of dogs with antebrachial fractures, greyhounds were over‐represented for the antebrachial injury (odds ratio 117, 95% confidence interval 13–1022). Five dogs sustained injury during exertional exercise or with relatively minor trauma. Submitted bone samples (n = 4) showed no evidence of underlying neoplasia. Mean followup was 15.5 months with 11 complications recorded in 7/8 dogs, including 1 catastrophic, 5 major, and 5 minor complications. Pancarpal arthrodesis allowed a full functional outcome in 3 dogs and an acceptable outcome in 3. Conclusion: Comminuted articular fractures of the distal radius and ulna are complex injuries and have a similar presentation to pathologic fractures. Surgical management by pancarpal arthrodesis is associated with a high risk of complication and a guarded prognosis for a full functional outcome.